What's the point of theology? : wisdom, wellbeing and wonder - McGrath, Alister E., 1953- (London SPCK, 2022)
"Theology is the study of the nature of God and of religious belief. But why should that matter to us? What's the point of theology? In this wonderfully accessible book, renowned theologian Alister McGrath answers that question--What's the point of theology?--and explores the depth and breadth theology can bring to our lives. Drawing on insights from his experience of coming to Christianity from atheism, this exhilarating and enlightening volume reveals how theology can help us grow in wisdom, contribute to our wellbeing, spark our innate sense of wonder, and above all, grow in faith and love as we draw ever closer to the divine. Ideal for new and seasoned Christians who want to engage more deeply with their faith, as well as those who are puzzled by spiritual matters and curious to find out more, What's the Point of Theology? will open your eyes to all that theology has to offer--a wiser understanding of what really matters, a richer vision of the good life, a deeper appreciation of the beauty of nature, and an avenue to strengthen your faith and relationship with God"--
Includes bibliographical references.
Keywords: Theology; RELIGION / Philosophy; RELIGION / Christian Theology / Systematic